The Influence Of Perceived Convenience On AI-Enabled Customer Experience In Shopee’s Chatbot With Perceived Sacrifice, Trust, And Customer Loyalty As Mediating Variables - Azmita Anvus Rosyada; Arif Hartono (UNIVED Press, 2025)
Various e-commerce platforms have integrated AI-based services, including Shopee. The most commonly used AI-based service is chatbots, which play a role in enhancing customer interaction and service efficiency. This study aims to examine how perceived convenience influences AI-enabled customer experience among Shopee chatbot users, as well as to explore the mediating roles of perceived sacrifice, trust, and customer loyalty in this relationship. This research employs a quantitative approach using the convenience sampling technique, collecting data from 243 Shopee chatbot users, which were analyzed using PLS-SEM. The results indicate that trust and customer loyalty have a significant direct impact on perceived convenience and AI-enabled customer experience, and also serve as mediators in this relationship. Meanwhile, the perceived sacrifice variable does not have a direct effect and does not mediate the relationship between perceived convenience and AI-enabled customer experience.